Treatment of asthma in a general practice. Issue 703 (May 1984) - Shee, C. D.; Poole, D.; Cameron, I. R.
Abstract : We examined the general practice treatment of 67 patients diagnosed as asthmatic. Compliance with treatment was poor in one-third of patients with severe asthma. Inhaled steroids were under-prescribed and our findings suggest that some severe asthmatics are receiving less than adequate therapy.